2012
DOI: 10.1007/s11357-012-9390-1
|View full text |Cite|
|
Sign up to set email alerts
|

RETRACTED ARTICLE: Aging decreases rate of docosahexaenoic acid synthesis-secretion from circulating unesterified α-linolenic acid by rat liver

Abstract: Docosahexaenoic acid (DHA,, an n-3 polyunsaturated fatty acid (PUFA) found at high concentrations in brain and retina and critical to their function, can be obtained from fish products or be synthesized from circulating α-linolenic acid (α-LNA, 18:3n-3) mainly in the liver. With aging, liver synthetic enzymes are reported reduced or unchanged in the rat. To test whether liver synthesis-secretion of DHA from α-LNA changes with age, we measured whole-body DHA conversion coefficients and rates in unanesthetized a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 62 publications
1
4
0
Order By: Relevance
“…Using the steady-state infusion method, we estimated synthesis rates of DHA from ALA to be 1.5 and 0.045 μmol/day in animals consuming the ALA and control diets, respectively. These rates are lower, but in line with previously published estimates using the steady-state infusion technique ( 24 , 43 , 44 ). Differences could be due to the fact that we performed the steady-state infusion in rats fed a diet containing 2% of the total fatty acids as ALA, whereas Gao et al ( 24 ) fed their animals a diet containing approximately 5% of the total fatty acids as ALA.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Using the steady-state infusion method, we estimated synthesis rates of DHA from ALA to be 1.5 and 0.045 μmol/day in animals consuming the ALA and control diets, respectively. These rates are lower, but in line with previously published estimates using the steady-state infusion technique ( 24 , 43 , 44 ). Differences could be due to the fact that we performed the steady-state infusion in rats fed a diet containing 2% of the total fatty acids as ALA, whereas Gao et al ( 24 ) fed their animals a diet containing approximately 5% of the total fatty acids as ALA.…”
Section: Discussionsupporting
confidence: 91%
“…This rate is only a measure of the synthesis rate in these rats at this time, when the rats are older and when the DHA synthesis rate is also likely low. It has been shown previously that the DHA synthesis rate decreases with age in rats ( 44 ).…”
Section: Discussionmentioning
confidence: 78%
“…Women also have a greater capacity than man to synthesise n-3 PUFA from their essential fatty acid precursor ALA [ 12 ]. Moreover, turnover of n-3 PUFA in plasma of old males decreased with age [ 13 ]. Furthermore, we have found strain- and sex-related differences in red blood cells levels of ALA, which was almost three times higher in female SHR than age-matched Wistar rats and comparing to males.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have suggested that the aging brain (22 month-old) is prone to lose DHA in rodents [24, 25]. The specific DHA deficiency in aged brain may result from an age-related reduction in the activity of the enzymes specifically regulating DHA synthesis in liver, as well as its uptake and assembly into brain phospholipids [2628]. Despite the age-related loss of DHA observed in rodents, dietary supplementation of DHA in aged rats can prevent such losses [29, 30].…”
Section: Impact Of Diet and Aging On Cerebral Pufas Contentmentioning
confidence: 99%